PENINGKATAN KETERAMPILAN MENULIS PUISI MENGGUNAKAN TEKNIK MIND MAPPING DI KELAS V SD. - Maistika Ratih; Taufina Taufina (JINoP (Jurnal Inovasi Pembelajaran), 2019)
Abstrak: Based on preliminary studies conducted in class V SDN 01 Koto Merapak. In indoensian language subjects, especially in writing poetry there are still many difficulties and obstacles faced by students. Students find it difficult to express their ideas in the form of poetry. This happens because the learning media used by educators is still less attractive to student, educators have not utilized the media as an object in writing poetry. This causes the skills of student in poetry to be low. The purpose of this study was to describe the improvement of poetry writing skills using the Mind Mapping technique in class V SDN 01 Koto Merapak.  This study uses a qualitative  and quantitative approach, with a type of classroom action research. This research was conducted in two cycles, with the stages of planning, implementing , observing and reflecting. This research was carried out inthe second semester of the 2018/2019 school year at SDN 01 Koto Merapak. With the subject of this research is the fifth grade students of SDN 01 Koto Merapak with a total of 32 student. While the research instruments are observation sheets, field note sheet test sheet, and documentation. The results showed that poetry writing skills using Mind Mapping techniques can improve poetry writing skills of students in SDN 01 SDN Koto Merapak. This can be seen from the result of the poetry  writing ability in the first ccle of meeting I getting an average of 69.78% with  the criterion (C), increasing in the first cycle of the first meeting obtaining an average of  74.12 % with the criteria of good (B), and increasing in the second cycle getting average –average 88.74% with very good criteria (SB). So based on the research above, that intellectual  ability in writing poetry can increase using the Mind Mapping technique.